Pendekatan pembelajaran pendidikan pancasila pada kurikulum merdeka; belajar pengembangan pada siswa sd/mi - Sha’af, Mohammad Adnan (Maliki Interdisciplinary Journal, 2026)
The purpose of this study is due to the importance of the role of teachers in shaping students through the Merdeka curriculum approach. The issues studied relate to the implementation of Pancasila Education in the Merdeka curriculum, which is able to develop the character and potential of students in the modern era. The goal is to understand Pancasila learning through the Merdeka curriculum and its impact on students related to its implementation. The Merdeka curriculum has a significant influence on student development today. This method uses a qualitative approach with a literature study approach through examining, reading, and reviewing several journals, articles, and books related to Pancasila education learning in the Merdeka curriculum. Through the results of the Merdeka curriculum study, students are able to increase student activeness, teacher creativity, and provide flexible and contextual learning spaces.